The study of ICT-use bybiology students before distance learning takes place during COVID-19 pandemic - Muhammad Luthfi Hidayat; Sukirman Sukirman (PROCEEDING UMSURABAYA, 2020)
Abstract. The study was carried out before the pandemic Covid-19 broke out, changing thecourse of lectures into distance learning. The initial idea of this study was to determine the intensity and familiarity of prospective Biology teacher students and their descriptions of how they used the Software in lecturing and completing Blended learning-based Microteaching assignments. This study also wants to illustrate the familiarity of respondents from some software that supports learning and teaching in Microteaching courses. All 71 respondents were undergraduate students, 88.7% were female, and 11.3% were male, aged between 18-23 years. Students must work on assignments given at the beginning of the semester to conduct teaching simulation (microteaching). Through this activity, students will gain their own experience to prepare their performance in microteaching, such as arranging lesson plans, developing learning media, and making presentations that are appropriate for their class. Therefore, the data collected meets the requirements for analysis using statistical Software. The study found that pre-service Biology teacher students have a high preference for the use of Android-based smartphones, Whatsapp, and internet cellular connectivity to fulfill their course work. The benefits of this research are media information or application materials that can be used in distance learning